2004
DOI: 10.1007/s00204-004-0546-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the carbamates fenoxycarb, propamocarb and propoxur on energy supply, glucose utilization and SH-groups in neurons

Abstract: Carbamates belonged to an older insecticide group, with propoxur being representative of this group. However, today carbamates with hormonal effects on insects, like fenoxycarb, or with fungicide properties, like propamocarb, are also used. The goal was a comparison of three structurally and functional different carbamates with a possibly common toxicological mechanism. Primary neuronal cell cultures of the rat are a well established model to identify neurotoxic compounds like n-hexane or acrylamide. In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…This can be accomplished because other than targeting on sodium channels of nervous system, pyrethroids possess toxic effects on cells such as inhibition of cell mitochondrial complex I or causing DNA damage and cell death (Gassner et al, 1997;Patel et al, 2007;Naravaneni & Jamil, 2005). Similar cell death and cytotoxic to cells caused by organophosphates and carbamate insecticides have also been reported (Maran et al, 2010;Schmuck & Mihail, 2004). This is supported by that we previously observed cytotoxic effects of deltamthrin on insect Sf9 cells.…”
Section: Use Of Cell-based Mtt Cytotoxicity Assays To Determine Insecsupporting
confidence: 68%
“…This can be accomplished because other than targeting on sodium channels of nervous system, pyrethroids possess toxic effects on cells such as inhibition of cell mitochondrial complex I or causing DNA damage and cell death (Gassner et al, 1997;Patel et al, 2007;Naravaneni & Jamil, 2005). Similar cell death and cytotoxic to cells caused by organophosphates and carbamate insecticides have also been reported (Maran et al, 2010;Schmuck & Mihail, 2004). This is supported by that we previously observed cytotoxic effects of deltamthrin on insect Sf9 cells.…”
Section: Use Of Cell-based Mtt Cytotoxicity Assays To Determine Insecsupporting
confidence: 68%
“…Likewise, toxic metal compounds inhibited DNA repair processes by binding to sulfhydryls (SH), thus causing protein denaturation and inhibiting enzyme activity . Reaction of carbamates with SH‐groups was clearly shown over a long‐term exposure period, but not after short‐term treatment . Recent reports also showed that redox changes affecting cysteines significantly decreases OGG1's activity .…”
Section: Discussionmentioning
confidence: 99%
“…Carbofuran impairs the energy state of neurons by inhibition of glycolysis and decreases ATP levels along with reduced dendritic length and spine density of pyramidal neurons in the hippocampus. It induces DNA fragmentation, resulting in apoptosis and loss of hippocampal neurons (23,25). It has also been reported that low-dose exposure of carbofuran causes changes in lipid composition and membrane-bound enzyme activity and also disturbs synaptosomal calcium homeostasis along with neurophysiological and neurobehavioral alterations in rodents (26 -28).…”
mentioning
confidence: 99%